IS ECONOMIC GROWTH AFFECTED BY BASIC INFRASTRUCTURE ? (STUDY CASE TERNATE NORTH MALUKU) - Runtunuwu, Prince Charles Heston (Citra Media Publishing, 2024)
This study aims to determine the effect of road infrastructure on economic growth, clean water infrastructure on economic growth and electricity infrastructure on economic growth. The data used is sourced from BPS Ternate City from 2009-2021. The research data used is quantitative data. The type of data used in this research is secondary data and time series. The testing technique used is multiple regression analysis. The test results of this study have a simultaneous effect on the three variables being tested. While partially testing the variables of road infrastructure, clean water and electricity effect on economic growth.